Selenoglutathione-Mediated Rescue of Kinetically Trapped Intermediates in Oxidative Protein Folding - Metanis, Norman; Foletti, Carlotta; Beld , Joris; Hilvert, Donald (Israel journal of chemistry, 2011)
Selenoglutathione has been shown to have considerable potential as a catalyst of oxidative protein folding. Here we examine how this reagent modulates the folding pathway of bovine pancreatic trypsin inhibitor (BPTI) and show that the diselenide increases the efficiency of this process primarily by accelerating the conversion of a kinetically trapped folding intermediate.